Looking for fun in Cultural Science - McKee Alan (Cultural Science)
There has been a tension in Cultural Studies between those authors who see fun as important; and those who see it as a distraction. This tension has been played out around the concepts of amusement, distraction, pleasure, celebration, playfulness and desire. I think that fun is important. As we move from Cultural Studies to Cultural Science, I want to retain a focus on fun.